2015
DOI: 10.1016/j.fertnstert.2015.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Adverse pregnancy and birth outcomes associated with underlying diagnosis with and without assisted reproductive technology treatment

Abstract: Objective To compare the risks for adverse pregnancy and birth outcomes by diagnoses with and without ART treatment to non-ART pregnancies in fertile women. Design Historical cohort Setting Massachusetts vital records linked to ART clinic data from SART CORS Patients Diagnoses included male factor (ART only), endometriosis, ovulation disorders, tubal (ART only) and reproductive inflammatory disorders (non-ART only). Pregnancies resulting in singleton and twin live births from 2004–08 were linked to hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
120
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(133 citation statements)
references
References 22 publications
11
120
2
Order By: Relevance
“…Endometriosis is associated with increased risks of antepartum bleeding and placental complications, irrespective of IVF treatment (31, 64). Our prior analyses of IVF pregnancies indicated that among all infertility diagnoses, endometriosis had the highest rates of uterine bleeding (4.8%) and placenta previa (2.4%) (34).…”
Section: Discussionmentioning
confidence: 99%
“…Endometriosis is associated with increased risks of antepartum bleeding and placental complications, irrespective of IVF treatment (31, 64). Our prior analyses of IVF pregnancies indicated that among all infertility diagnoses, endometriosis had the highest rates of uterine bleeding (4.8%) and placenta previa (2.4%) (34).…”
Section: Discussionmentioning
confidence: 99%
“…During the study period, 72 pregnancies from 67 women with colorectal endometriosis were recorded ( Table 1). The median age (range) of the women was 31 (23-43) years and median body mass index (BMI) (range) was 21.7 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) kg/m 2 . Forty-four of the 67 (66%) women had a documented infertility.…”
Section: Epidemiological and Surgical Characteristics Of The Populationmentioning
confidence: 99%
“…The median delivery gestational age (range) was 39 (33)(34)(35)(36)(37)(38)(39)(40)(41)(42) weeks. There were 70 singleton pregnancies and two twin pregnancies (Tables 2 and 3).…”
Section: Delivery Outcomes Of the Populationmentioning
confidence: 99%
“…However, recent reviews and meta-analysis have shown that singletons conceived by IVF are prone to higher rates of adverse pregnancy outcomes including low birthweight (LBW), preterm deliveries (PTL) and congenital malformation compared with spontaneously conceived singletons (Hansen et al, 2013;Henningsen et al, 2011;Schieve et al, 2002;Wang et al, 2005). Whether this adverse outcome is related to the IVF treatment or to the underlying subfertility itself is unclear (Jaques et al, 2010;Stern et al, 2015;Zhu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%